(untitled) (International Journal of Medical and Surgical Sciences, 2019)
This study aims at determining the diagnostic value of peripheral lymph node biopsy and common causes of lymph node enlargement from biopsies obtained from patients with lymph-node enlargement at different sites in a teaching hospital in north central Nigeria town of Makurdi, Benue State. This is a retrospective study of surgical peripheral lymph node biopsies received in the department of Anatomic Pathology, Benue State University Teaching Hospital, Makurdi, Nigeria from February, 2012 to September, 2019. Total number of lymph node biopsies during the period was 47 representing 1.0% of surgical pathology specimens submitted to the department; 25 cases were females and 22 were males. Metastatic nodal involvement (57%), lymphoma (23%) and tuberculosis lymphadenitis (11%) were the most common causes of lymph node enlargement. All the studied nodes were localized. The most common sites of lymphadenopathy were axillary (21%), cervical (16%) and Inguinal (6%). While axillary lymph node enlargements were mostly associated with tumor metastasis, cervical and inguinal node enlargements were mostly associated with tuberculosis and lymphoma, respectively. Surgical excision of nodal enlargement for histological examination represents a simple, good diagnostic yield with lack of significant morbidity or mortality.